Localized hamstring bioimpedance in marathon runners is related to muscle high-energy enzyme serum levels and predicts race time - Nescolarde, Lexa; Yanguas, Javier; Hernández-Hermoso, José A. (Frontiers in Physiology, 2024)
The aim was to analyze the response of serum levels of inflammatory, high-energy muscle biomarkers and hamstring localized bioimpedance (L-BIA) measurements to marathon running and to ascertain whether they correlate with each other or with race time. Blood samples and hamstrings tetra-polar L-BIA measurements from 14 Caucasian male recreational athletes at the Barcelona Marathon 2019 were collected at base line, immediately after and 48 hours post-race. Serum C reactive protein (sCRP), creatinine kinase (sCK) and lactate dehydrogenase (sLDH) were determined using an AU-5800 chemistry analyzer. L-BIA was obtained at 50 kHz with a Quantum V Segmental phase-sensitive bioimpedance analyzer. Median sCRP increased (4-fold) after 48h post-race. Median sCK and sLDH levels increased immediately post-race (3-fold, 2-fold) and 48h post-race (5-fold, 1fold). Left, right and combined hamstring reactance (Xc) and phase angle (PhA) increased immediately post-race. Xc combined hamstring pre-and immediately post-race correlated with racetime and with sCK and sLDH median levels pre-race. Xc combined hamstring pre-and immediately post-race > 15.6  and 15.8 , respectively, predicted the race time of 3:00:00 h. L-BIA reactance (Xc) is an objective direct, real time, easy, noninvasive bioelectrical parameter that may predict muscle and marathon athlete performance.